2018
DOI: 10.1007/s00418-018-1757-7
|View full text |Cite
|
Sign up to set email alerts
|

Histological processing of un-/cellularized thermosensitive electrospun scaffolds

Abstract: Histological processing of thermosensitive electrospun poly(ε-caprolactone)/poly( l -lactide) (PCL/PLA) scaffolds fails, as poly(ε-caprolactone) (PCL) is characterized by its low-melting temperature (Tm = 60 °C). Here, we present an optimized low-temperature preparation method for the histological processing of un-/cellularized thermosensitive PCL/PLA scaffolds. Our study is aimed at the establishment of an optimized dehydration and low-melting-point paraffin-embedding method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…PCL is biodegradable with slow degradation rates in vivo [23,24] and PCL-based materials for medical devices such as Capronor, a subdermal implant for long-term drug delivery [25] or drug delivery systems for glaucoma treatment [26] are already in clinical use or trial. Studies show that surface modification with fibronectin or blending with polylactide acid (PLA) improve cell attachment of endothelial cells or cell infiltration with trophoblast cells [27,28] as well as osteogenic and tenogenic differentiation of C3H10T1/2 pluripotent stem cells [29]. Furthermore, PCL-PLA and PCL-gelatine fibre mats seeded with mesenchymal stem cells showed high biocompatibility with viabilities higher than 82% after seven days as reported by Gryshkov and coworkers [30].…”
Section: Introductionmentioning
confidence: 63%
“…PCL is biodegradable with slow degradation rates in vivo [23,24] and PCL-based materials for medical devices such as Capronor, a subdermal implant for long-term drug delivery [25] or drug delivery systems for glaucoma treatment [26] are already in clinical use or trial. Studies show that surface modification with fibronectin or blending with polylactide acid (PLA) improve cell attachment of endothelial cells or cell infiltration with trophoblast cells [27,28] as well as osteogenic and tenogenic differentiation of C3H10T1/2 pluripotent stem cells [29]. Furthermore, PCL-PLA and PCL-gelatine fibre mats seeded with mesenchymal stem cells showed high biocompatibility with viabilities higher than 82% after seven days as reported by Gryshkov and coworkers [30].…”
Section: Introductionmentioning
confidence: 63%
“…In one previous report, transplanted and harvested tissue-engineered constructs were fixed in formalin and embedded in paraffin using PCL/PLLA fibrous scaffolds, after which tissues were analyzed by IHC [ 29 ]. However, another study reported that histological processing of thermosensitive PCL/PLL scaffolds fails because of the low-melting temperature (T m ≈ 60 °C) characteristic of PCL [ 30 ]. To circumvent this problem, the authors combined PLC with a low-melting-point paraffin-embedding method for histological investigations of thermosensitive specimens [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed electrospun scaffolds consisting of an inner layer of PCL/PLA (100/50 mg/ml) and an outer layer of PCL (200 mg/ml). These scaffolds showed good cell adherence but were thermosensitive and needed a lowtemperature preparation method for histological processing (Fuchs et al, 2019). Fuchs et al showed that the combination of low-melting-point paraffin embedding and pepsin digestion can be used as an antigen retrieval method for histological FIGURE 6 | Cell tracking in hAMSC-treated wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The fiber morphology of the scaffolds was characterized using scanning electron microscopy (VP-SEM S3400, Hitachi Europe). Six samples were taken from each fiber mat and coated with gold palladium (Sputter Coater SC7620, Emetich) for 45 s. Images were acquired and analyzed according to a standard operating procedure (Fuchs et al, 2019). Fiber diameter distribution and mass of samples were used to calculate the specific surface of the electrospun scaffolds using the following equations:…”
Section: Materials Characterization Of Pcl/pla Scaffolds and Collagen-mentioning
confidence: 99%